The Impact of Celiac Disease on Caregivers' Well-being: An Integrative Review. Issue 3 (March 2020) - Satherley, Rose-Marie; Coburn, Shayna S.; Germone, Monique
ABSTRACT: Objectives: A diagnosis of celiac disease (CD) requires individuals to adopt a strict gluten-free diet. As children with CD must rely on their caregivers for guidance and support with managing the gluten-free diet, CD may challenge the caregiver's emotional and social well-being. The primary objective of this mixed-methods systematic review was to synthesize research investigating the impact of CD on caregiver's well-being. Methods: Five databases were systematically searched from 1990 to 2018 to identify all empirical studies that assessed well-being in caregivers of children (0–18 years) with CD. Qualitative and quantitative data were extracted separately before being integrated to explore key themes across the studies. Results: Twelve studies were identified that explored the well-being of caregivers of children with CD (3 qualitative, 9 quantitative), reporting on 665 caregivers. The quality of evidence was limited across studies. Synthesis of results revealed 3 themes ( Caregiver Responsibility, Caregiver Well-Being and Concern for Child's Health, Implications for the Family ) describing the impact of a child with CD on caregiver well-being. Conclusions: Caregivers of children with CD may experience difficulties that impact their well-being; specific difficulties identified included the impact of caregivers' social activities, finances, and anxiety. The findings detailed in this review point toward factors that may guide health care personnel to provide support for the caregivers of children with CD.